2018
DOI: 10.5194/bg-15-5929-2018
|View full text |Cite
|
Sign up to set email alerts
|

Reviews and syntheses: Carbon use efficiency from organisms to ecosystems – definitions, theories, and empirical evidence

Abstract: Abstract. The cycling of carbon (C) between the Earth surface and the atmosphere is controlled by biological and abiotic processes that regulate C storage in biogeochemical compartments and release to the atmosphere. This partitioning is quantified using various forms of C-use efficiency (CUE) – the ratio of C remaining in a system to C entering that system. Biological CUE is the fraction of C taken up allocated to biosynthesis. In soils and sediments, C storage depends also on abiotic processes, so the term C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 89 publications
2
121
0
Order By: Relevance
“…The fungal cell wall is essentially composed of two polymers; β-1,3-glucan, polymerized by glucan synthase (GT48), and chitin, polymerized by chitin synthase (GT2) (Bowman and Free, 2006). The carbon (C) use efficiency represents the proportion of acquired carbon that the organisms use to build biomass (Manzoni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungal cell wall is essentially composed of two polymers; β-1,3-glucan, polymerized by glucan synthase (GT48), and chitin, polymerized by chitin synthase (GT2) (Bowman and Free, 2006). The carbon (C) use efficiency represents the proportion of acquired carbon that the organisms use to build biomass (Manzoni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We expected that the differences in decomposer capacity and ecology would be reflected in the genomes, in the expression of genes central for the decomposition machinery, as well as in the expression of genetic markers related to C use efficiency (CUE). C use efficiency should decrease with time, due to increased costs of mycelial maintenance and the more complex decomposing machinery required as the substrate becomes increasingly recalcitrant (Manzoni et al, 2018). Furthermore, C use efficiency was expected to be lower for C. longipes, as its stress-tolerant mycelium should have a higher cost of maintenance relative to its slow growth, compared with the rapidly growing G. androsaceus [c.f.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted laboratory experiments using an isotope tracer at a range of substrate availabilities (C:P ratios of 7:1, 60:1 and 200:1) to explore the effects of different redox conditions and substrate stoichiometry on microbial P utilization. We used C use efficiency (CUE), the partitioning of organic C allocated to microbial growth vs. respiration, as an index of the conversion efficiency of detrital organic matter to microbial biomass (Manzoni et al ; ). Microbial CUE controls the conversion of plant C to microbial C, and thus affects ecosystem C storage as well as the flow of energy and materials through the soil food web (Sinsabaugh et al ).…”
Section: Introductionmentioning
confidence: 99%
“…However, radial growth of black spruce trees clearly declined with organic layer thickness, resulting in different tree aboveground biomass between the study sites. This underlines that changes in iWUE are not necessarily related to changes in carbon use efficiency because of site conditions (Manzoni et al 2018). Consequently, dynamic changes in edaphic conditions need to be considered in process models (Guiot et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While the impacts of paludification on stem growth are well understood, forest ecophysiological mechanisms associated with growth decline remain unknown at the stand scale. In non-paludified forests, an increase in tree intrinsic water use efficiency (i.e., the ratio of carbon assimilated to water losses through evapotranspiration; Farquhar et al 1989) associated with rising ambient CO 2 concentration has commonly been reported without enhancing carbon use efficiency (Manzoni et al 2018) or tree radial growth (e.g., Peñuelas et al 2011;Silva and Horwath 2013;Lévesque et al 2014). Indeed, while photosynthesis stimulation and stomatal conductance reduction control changes in water use efficiency, stem growth appears to be limited by local edaphic factors, such as nutrient availability (e.g., nitrogen).…”
mentioning
confidence: 99%